Answer:
(2,-3)
Step-by-step explanation:
I am not sure if you meant the first equation to be y or -y. I solved it as y.
y = x-5 -x -3y =7
I am going to take the second equation and write it as x =
-x - 3y = 7 Give equation
-x = 3y +7 Add 3y to both sides
x = -3y-7 Multiplied each term in the equation by -1 so that x could be positive
I am going to substitute -3y-7 for x in the first equation up above
y = x - 5
y = -3y -7 - 5 Substitute -3y-7 for x
y = -3y -12 Combined -7-5
4y = -12 Added 3y to both sides
y = -3 Divided both sides by 4.
I now know that y is -3, I will plug that into x = -3y-7 to solve for x
x = -3(-3) -7
x = 9-7 A negative times a negative is a positive
x = 2
(3.5×10^(8))÷(6.6×10^(4))
=5,303.0303030303
answer : b
X^2-4x=-2x+24
x^2-2x=24
x^2-2x-24=0
(x-6)(x+4)
Proof:
-6+4=-2
-6*4=-24
Final answer: (x-6)(x+4)
If x is number of hours worked and y total pay, in y=9.5x, 9.5 is hourly rate.
Isa's hourly rate is 9.5$.
From the table: for 2 hours worked Jack earns 16.5$, for 5 hours worked 41.25$ and for 8 66$. Jack's hourly rate is 16.5$/2=8.25$.
9.5/8.25=1.15
Isa earns 9.5$ per hour and Jack earns 8.25$ per hour. Isa's hourly rate of pay is 1.15 Jack's hourly rate of pay.
Answer:
w=-5
Step-by-step explanation:
3w=-18+3
3w=-15
w=-5